Degraded Hyaluronic Acid-Modified Magnetic Nanoparticles. (11th February 2020) - Nie, Wan; Zhang, Baolin; Yan, Xianjia; Su, Lichao; Wang, Sheng; Han, Guihua; Han, Dong
Abstract : Superparamagnetic iron oxide nanoparticles (SPIONs) conjugated with hyaluronic acid (HA) functional groups have potential applications as cell targeting materials. However, SPIONs incubated with high-molecular weight HA can result in severe agglomeration. In this work, we found that when modified with degraded HA (hyaluronan oligosaccharides (oHAs)), the nanoparticles were uniformly dispersed with small hydrodynamic sizes, and the oHA-modified SPIONs exerted minimal cytotoxicity. With the same functional groups as HA, the oHA-modified SPIONs may have various biomedical applications.